The Correlation of Lavender Aromatherapy with The Childbirth Process in The Independent Practice of Midwives - Saraswati, Ni Putu Ayu Tumbu; Ariyani, Ni Wayan; Purnamayanti, Ni Made Dwi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Prolonged labor is one of the causes of high Maternal Mortality Rate (MMR) in the world. Prolonged labor has an average cause of maternal death worldwide by 8% and in Indonesia by 9%. Prolonged labor can be prevented with several efforts, namely by using various proven pharmacological and non-pharmacological methods, which are used to shorten the labor process. Lavender aromatherapy is a well-known complementary medicine with a calming effect. Lavender essential oil, used as aromatherapy for analgesics, contains 8% terpenadan and 6% ketones. This study aims to determine the relationship between lavender aromatherapy and the labor process in the Independent Midwife Practice in Denpasar City. This type of research was a correlation analysis using a cross-sectional design. The research conducted in February-April 2023 with 55 respondents used simple random sampling. The instrument used in this study was a data collection format. The data analysis used was the Chi-Square test, and the Chi-Square statistical test was 0,004 (<0,05) so that the hypothesis can be accepted and it can be concluded that there was a relationship between lavender aromatherapy and the labor process in Independent Midwife Practices in Denpasar City. Independent Midwife Practices in Denpasar City were expected to apply complementary lavender aromatherapy therapy to provide obstetric care for labor.Â